A survey of police officers encounters with sober, alcohol- and drug-intoxicated suspects in Sweden. Issue 5 (28th May 2022) - Hagsand, Angelica V.; Evans, Jacqueline R.; Pettersson, Daniel; Schreiber Compo, Nadja
ABSTRACT: Alcohol-related crimes are very common globally, including in Scandinavia. Despite this, no survey to date has examined the prevalence of alcohol- and drug-intoxicated suspects in Sweden specifically, or which procedures police use when interacting with this suspect group. Given the current lack of (inter)national policy guidelines on how to interrogate intoxicated persons, it is important to examine law enforcement's contact with this potentially vulnerable group in different contexts. This was the aim of the present study. Data were collected via an online survey sent out to Swedish police investigators and 133 officers responded in total. A large majority (87%) of responses indicated that it was common or very common to encounter intoxicated suspects, but findings also suggest that police departments differ in their procedures for when and how to conduct investigations and interviews involving drunk suspects. Our findings support the need for (inter)national guidelines on how to interview intoxicated suspects and the need for more scientific studies on how alcohol affects suspect's memory and decision making.